Zero-Contrast Multivessel Revascularization for Acute Coronary Syndrome in a Patient With Chronic Kidney Disease - Madhavan, Mahesh V. (JACC Case Rep, 2019)
Patients with chronic kidney disease are at elevated risk for adverse events after traditional coronary angiography and percutaneous intervention with contrast media. The case presented in this report highlights the potential benefits of zero-contrast multivessel percutaneous coronary intervention in a patient presenting with a non–ST-segment elevation acute coronary syndrome. (Level of Difficulty: Beginner.)